Rechargeable lithium film batteries: encapsulation and protection - Ribeiro, J. F. (2012)
Rechargeable solid-state lithium batteries were developed before [1] by physical vapour deposition (PVD). These batteries are fabricated with lithium-cobalt oxide (LiCoO2), lithium-phosphorus oxynitride (LiPON) and lithium (Li), respectively for cathode, electrolyte and anode. The LiCoO2 and LIPON were deposited by RF sputtering and the metallic Li by thermal evaporation. The chosen material for current collectors was titanium (deposited by e-beam technique) to prevent chemical reactions in contact with lithium and provide good electrical conductivity. In this work, the protection of lithium films from oxidation and delithiation is presented. Ti, LiPON, LiPO and layered films combining these materials were compared as protection for lithium. Titanium and LiPO films show good results and potential to be used as short-term protective materials in lithium batteries.